Ministry Of Tourism Decree No. 212 Of The Year 2013 Issued On 6/3/2013 = وزراة السياحة قرار رقم 212 لسنة 2013 صادر بتاريخ 6/3/2013 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.